Keabsahan Talak Cerai melalui Whatsapp Perspektif Madzhab Syafi’i - Imam Mahfudz Imanan; Basit Misbachul Fitri; Sukandar Sukandar (STAI Hidayatut Thullab Kediri, 2024)
Households will inevitably encounter problems and issues. The problems experienced are sometimes quickly resolved, but often these issues cannot be unraveled, leading to an unavoidable fracture in the household. Islam provides a solution when the household can no longer be maintained. The solution offered is to perform a divorce (talak) in a manner that is considered ma'ruf. Currently, knowledge and information technology are developing very rapidly, bringing a new paradigm in understanding various issues that arise among Muslims. One of the issues that might be affected is the problem of divorce, which in classical times was only done by the husband directly pronouncing the divorce statement to his wife or at most by writing it on a piece of paper. However, in contemporary times, divorce can be done through various electronic media. In this thesis, the author discusses the opinions of Imam al-Nawawi and Imam al-Imroni with the following problem formulation: first, what is Imam al-Nawawi's view on divorce through WhatsApp Second, what is Imam al-Imroni's view on divorce through WhatsApp? Third, how does the comparison between the views of Imam al-Nawawi and Imam al-Imroni regarding divorce through WhatsApp. To obtain answers to the formulated problem, the author uses a library research method with a qualitative approach. The primary sources in this study are the book Al-Majmu’ Syarh Al-Muhazzab by Imam al-Nawawi and the book al-Bayan fi al-Madzhab Imam al-Syafi’i by Imam al-Imroni, while the secondary sources are obtained from various literatures that are relevant to the issues being researched. The data collection technique was carried out through documentation. Meanwhile, the data analysis methods used by the author are content analysis and comparative methods. The research results show that divorce through written messages, which can be related to modern written message media, is validated by Imam al-Nawawi, with the consideration that the status of writing, which consists of letters that can be understood in form and meaning, is the same as the status of words spoken by the tongue and is permissible even if not in one gathering. According to Imam al-Imroni, it is not valid because, in his view, a letter or written message is like something that does not exist (is not visible) and must be done in one sitting. As for the similarity, both must use intention in the implementation of divorce through written messages